2004
DOI: 10.1645/ge-291r
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii in Wild Toque Macaques (Macaca sinica) at Polonnaruwa, Sri Lanka

Abstract: From a natural population that inhabits the dry evergreen forest at Polonnaruwa, serum samples of 170 toque macaques were examined for antibodies to Toxoplasma gondii by the modified agglutination test. Of these, 21 (12%) were found with titers of 1:16 in 9, 1:32 in 9, 1:256 in 1, 1:1,024 in 1, and 1:4,096 in 1. There was no evidence of maternal transmission of antibodies or congenital toxoplasmosis. None of the infected macaques died within 1 yr after sampling. Toxoplasma gondii infection was closely linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Both Ekanayake et al (2004) and Garcia et al (2005) observed significant risk of the occurrence of toxoplasmosis in humans by the analysis of nonhuman primate serum samples, considering these primates as sentinels to human infection, once they have access to human places, and eating fruits and vegetables contaminated with oocysts from the soil and demonstrate the risk to human infection by these type of food in urban, rural and wild areas. In some urban, rural and wild areas, some of them indigenous, nonhuman primates are hunted and used as food, one more example of the risk to human infection and importance as sentinels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Ekanayake et al (2004) and Garcia et al (2005) observed significant risk of the occurrence of toxoplasmosis in humans by the analysis of nonhuman primate serum samples, considering these primates as sentinels to human infection, once they have access to human places, and eating fruits and vegetables contaminated with oocysts from the soil and demonstrate the risk to human infection by these type of food in urban, rural and wild areas. In some urban, rural and wild areas, some of them indigenous, nonhuman primates are hunted and used as food, one more example of the risk to human infection and importance as sentinels.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with other studies, using other nonhuman primates than tufted capuchin monkeys, different prevalence were observed by Garcia et al (2005) studying black and golden howler monkeys, Alouatta caraya (3/17, 17.6%), by Cadavid et al (1991) studying Cebus albifrons (9/22, 40.9%) Frequency of Toxoplasma gondii antibodies in tufted capuchin monkeys (Cebus apella nigritus) from an ecological station in Brazil and C. capucinus (2/15, 13.3%), by Sanchis et al (1972) studying Alouatta fusca (5/12, 41.7%), by Li et al (2010) studying bred cynomolgus monkeys, Macaca fascicularis (5/360, 1.4%) in China, and by Ekanayake et al (2004) studying toque macaques, M. sinica, (21/170, 12%) in Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
“…Natural infection with Toxoplasma gondii has been noted in several species of Asian macaques, most recently in Toque macaques (M. sinica) from Sri Lanka (Ekanayake et al 2004). Infection is closely linked to human environments where domestic cats are common.…”
Section: Toxoplasmosis (Toxoplasma Gondii)mentioning
confidence: 99%
“…Snares set for bush meat trap other animals, including leopards (Kittle et al 2014). Humans and their domestic animals also have introduced disease, such as toxoplasmosis (Ekanayake et al, 2004), cryptosporidiosis and a variety of enteric parasites into wild populations of primates (Ekanayake et al, 2006(Ekanayake et al, , 2007.…”
Section: Human-animal Conflict and Misconceptionsmentioning
confidence: 99%